2016
DOI: 10.1016/j.msard.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB*1501 associations with magnetic resonance imaging measures of grey matter pathology in multiple sclerosis

Abstract: Background: The HLA-DRB*1501 haplotype influences the risk of developing multiple

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Interestingly, HLA-DRB1*15:0 1 and DRB1*04:05 differentially influenced ICLs in our patients; the former increased ICLs and the latter decreased them. No difference was observed between patients with and without DRB1*15:01 in phase-sensitive inversion recovery MRI measurements, 31 whereas pathologically DRB1*15 carriers exhibited more severe parenchymal, perivascular, and meningeal T cell inflammation than those without the allele. 32 Although it is possible that DRB1*15:01 facilitates ICL development in Japanese MS patients, our multiple logistic regression analysis revealed that only DRB1*04:05 exhibited a primary significant decreasing effect on ICLs.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, HLA-DRB1*15:0 1 and DRB1*04:05 differentially influenced ICLs in our patients; the former increased ICLs and the latter decreased them. No difference was observed between patients with and without DRB1*15:01 in phase-sensitive inversion recovery MRI measurements, 31 whereas pathologically DRB1*15 carriers exhibited more severe parenchymal, perivascular, and meningeal T cell inflammation than those without the allele. 32 Although it is possible that DRB1*15:01 facilitates ICL development in Japanese MS patients, our multiple logistic regression analysis revealed that only DRB1*04:05 exhibited a primary significant decreasing effect on ICLs.…”
Section: Discussionmentioning
confidence: 74%
“…24 A recent MRI study of 85 patients with MS did not reveal a statistically significant difference between HLA-DRB1*15:01 carriers and noncarriers; however, the authors point out the limited power due to the small number of cases. 25 Furthermore, meningeal inflammation and follicle-like structures in the meninges have been linked to microglia activity 22 and larger subpial cortical gray matter lesions. 26 Regarding expression of the 2 DR15 alleles, higher messenger RNA expression of DRB5*01:01 compared with DRB1*15:01 in MS lesions and normal-appearing white matter have already been observed previously supporting our findings; however, much fewer cases and neither gray matter nor the extent of demyelination had been studied.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8][9] Studies investigating the influence of HLA-DRB1*1501 on MRI-detected brain and spinal cord pathology in clinically isolated syndrome (CIS), relapsing-remitting MS (RRMS) and primary progressive MS (PPMS) have produced conflicting findings. [10][11][12][13][14][15][16][17][18][19] Some studies have found higher T2-hyperintense lesion load 10,[13][14][15]17 , brain atrophy 12,13,20 , and microstructural tissue damage 13,17 in HLA-DRB1*1501-positive compared with HLA-DRB1*1501-negative patients, but others have not. 16,18,19 Previous studies have mainly been cross-sectional in nature and included heterogeneous cohorts of patients with varying disease duration, clinical course and exposure to disease-modifying therapies, potentially accounting for these conflicting findings.…”
Section: Introductionmentioning
confidence: 99%